A Century of Psychotherapy in Argentina: Clinical Psychology, Psychoanalysis and Recent Developments - Fierro, Catriel; Fernández Álvarez, Javier; Manzo, Gustavo Adrián (Revista de Psicología, 2019)
Argentina owns an authentic psychotherapeutic culture, being psychoanalysis its most spread expression, particularly in public-managed universities. Nevertheless, Argentina lacks of a system to provide appropriate and continuous education for psychotherapists. Thus, psychologists’ abilities have been repeatedly described as biased and deficitary. Adopting a socio-professional historiographic framework, this study presents an historical overview and analysis of the development of the heterogeneous psychotherapeutic spheres in Argentina during the twentieth century, aim-ing to grasp and retrospectively explain the field’s present state. Argentinian psychotherapy is first described, from around 1900, when psychiatrists and physicians inaugurated and dominated the field, up to 1930, when psychoanalysis, reflexology and existentialism coexisted as clinical perspectives. The period between 1940 and 1970, char-acterized by psychoanalysis’ institutionalization, is then analyzed. The arrival of psychoanalysis at the newly created psychology careers, the professional disputes started by such arrival and the consequent hegemonization of the theory and its therapeutic outlook are emphasized. The period from 1970 onwards is detailed, describing institutional and professional developments. The development of systemic, cognitive and integrative approaches is detailed. Finally, contemporary challenges of the psychotherapy in Argentina are discussed, emphasizing the necessity of a deep debate based on historical and empirical evidence.